Chronic Myeloid Leukemia Relapsing 25 Years after Allogenic Stem Cell Transplantation - Håkon Reikvam; Jørn Skavland; Stein-Erik Gullaksen; Randi Hovland; Tobias Gedde-Dahl; Øystein Bruserud; Bjørn Tore Gjertsen (Case Reports in Hematology)
Chronic myeloid leukemia (CML) is a myeloproliferative disorder in which neoplastic cells exhibit the Philadelphia chromosome and the related oncoprotein BCR-ABL1. Allogeneic stem cell transplantation (allo-SCT) was considered the first-line treatment for CML, before the introduction of tyrosine kinase inhibitors (TKIs). However, patients are at risk for relapse years after transplantation. We present a patient who relapsed 25 years after allo-SCT for chronic phase CML. Polymerase chain reaction (PCR) detected gradually evaluated levels of BCR-ABL1 transcripts, eventually leading to the diagnosis of relapsed disease. Additional mutational analyses did not reveal mutations in the BCR-ABL1 gene, or other cooperating mutations. The patient was successfully treated with imatinib 400 mg daily, leading to new molecular remission. The case presentation emphasizes the need for long-term follow-up of such patients and the potential benefit of initiating TKI treatment with early signs of relapse.